The Impact Of Covid-19 On The Mental Health Of School Children Using The Children Depression Inventory (CDI) Instrument: Mental Health Of School Children - Anisa Purnamasari; Wa Ode Aisa Zoahira; Zahalim Zahalim; Asbath Said; Yulli Fety; Merry Pongdatu (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2023)
Background: Educational services aimed at children of all ages are still not fully open, and teaching and learning activities from elementary grades onward are still being provided alternately offline and online. More than 2.2 billion children in the world, which is about 28% of the world's child population, experience changes in mental health. COVID-19 has affected the lives of children and young people like never before. Children may be more vulnerable than others to the psychosocial effects of a pandemic. This can hinder children's growth and development, eliminate children's opportunities to manage stress, and cause social isolation. This study aims to look at the relationship between post-COVID-19 impacts and the mental health of school-age children using the Children's Depression Inventory (CDI). Methods: This research is a cross-sectional study using a conclusive research design aimed at examining a phenomenon through hypothesis testing. Data collection was carried out at 38 Public Elementary School, Kendari City, Southeast Sulawesi. The convenience sampling technique is used to select research respondents. Data collection used the Children's Depression Inventory (CDI) questionnaire. Results: The results of the study obtained a p-value of 0.000 where 0.05, indicating a significant relationship between post-Covid-19 responses and the mental health impact of school-age children using the Children's Depression Inventory (CDI) at 38 Public Elementary School, Kendari City. Conclusion: Based on the results of this study, the mental health of school-age children needs to be one of the elements included in the nursing care process that will be provided by nurses.